Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpca.6b04367
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Singlet Fission in a Structurally Well-Defined Norbornyl-Bridged Tetracene Dimer

Abstract: The photophysics of a norbornyl-bridged covalent tetracene (Tc) dimer BT1 and a monomer analogue Tc-e were studied in room-temperature nonpolar solvents. Notably in BT1, a Davydov-split band is observed in UV absorption, heralding interchromophore electronic interactions. Emission spectra indicate an acene-like vibronic progression mirroring the lowest-energy visible absorption. For BT1, this argues against excited-state excimer formation. Evidence of intramolecular singlet fission (SF) comes from a comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(125 citation statements)
references
References 79 publications
7
118
0
Order By: Relevance
“…Namely, we have previously argued for BT1 that λ for the diabatic S 0 S 1 → 1 TT may be larger, of order 0.5 eV. 9 The origin of this prediction is in calculations we made using structures from DFT and TD-DFT with gradients, that predicted a significant intramolecular (inner-sphere) reorganization energy λ i = 0.43 eV (S 1 → Q). Given the current results, this may be an overestimation.…”
Section: Figure 5 (A) Tripletmentioning
confidence: 92%
See 1 more Smart Citation
“…Namely, we have previously argued for BT1 that λ for the diabatic S 0 S 1 → 1 TT may be larger, of order 0.5 eV. 9 The origin of this prediction is in calculations we made using structures from DFT and TD-DFT with gradients, that predicted a significant intramolecular (inner-sphere) reorganization energy λ i = 0.43 eV (S 1 → Q). Given the current results, this may be an overestimation.…”
Section: Figure 5 (A) Tripletmentioning
confidence: 92%
“…As we have previously described for related systems, the symmetry of this dimer and the fact that the S 1 ←S 0 is acene short-axis polarized, means that only the higherenergy excitonic transition in a Davydov-split pair is bright. 9,13,18 In other words, this system is an H-type aggregate with respect to the S 1 ←S 0 transition of each chromophore arm. To the blue and peaked at 444 nm is a second progression that is also observed in monomer models such as TIPS-Pentacene (TIPS-Pc).…”
Section: Tips-bp1'mentioning
confidence: 99%
“…Many of these syntheses rely on metal-catalyzed cross-coupling protocols such as the Suzuki and Sonogashira reactions, althoughi nnovatives ynthe-ses based on, for example, Diels-Alder cycloadditions [53] have recently appeared. Beyond pentacene, av ariety of other carbon-rich oligomeric chromophores have been explored for iSF and contribute to unraveling the underlying mechanism, these reports are outside the scope of this Minireview,a nd for current examples, see references [54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…15,19,22,[34][35][36][37][38][39][40] As another way of controlling electronic coupling, the use of covalently-linked systems is promising because the electronic coupling can be designed at the molecular level. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] In the previous study, we proposed several ways of tuning electronic coupling concerning SF based on the quantum interference. 52 We observed that covalently-linked systems with constructive quantum interference induce faster SF than those with destructive quantum interference.…”
Section: Introductionmentioning
confidence: 99%